Trabalho em turno, estresse psicossocial no trabalho e sindrome metabólica: uma análise seccional do estudo ELSA Brasil - Aline Eliane dos Santos (2017)
BACKGROUND: Society is moving towards a 24-hour work pattern, with continuous growth in the supply of uninterrupted services and the consequent increase in demand and shift work. Night work has been touted as the trigger for various health problems, such as metabolic disorders, cardiovascular and mental illness. Additionally, the imbalance between psychological demand and control over work activities contribute to the development of psychosocial stress at work that affects the physical and mental health of the worker. It is also possible that the simultaneous presence of these two occupational exposures may potentiate the occurrence of health events. Previous studies have indicated that metabolic and endocrine changes triggered by exposure to night work and psychosocial stress at work may influence the development of metabolic syndrome and chronic noncommunicable diseases. The two hypotheses investigated were: 1) night work and psychosocial stress at work are independently associated with the metabolic syndrome and 2) the presence of psychosocial stress at work can modify the effect of night shift work on the occurrence of the metabolic syndrome. OBJECTIVE: Investigate the independent association of night work and psychosocial stress at work with the presence of metabolic syndrome in a large sample of public servants from six teaching and research institutions. Additionally, we investigated the presence of psychosocial stress modification at work in the association between night work and metabolic syndrome. METHODS: A cross-sectional analysis was performed using baseline data (2008-2010) from the Longitudinal Adult Health Study (ELSA-Brazil), a multicentre prospective cohort of public servants from six teaching and research institutions. Almost 12,000 active servers were included. Metabolic syndrome was defined according to the criteria of the National Cholesterol Education Program Adult Treatment Panel (NCEP-ATP III). The shift work was categorized according to the predominant shift in: always diurnal (reference), ex-night and current day, current night 20 years and current night> 20 years. Psychosocial stress at work was obtained through the Swedish Demand-Control-Support Questionnaire (DCSQ), based on Karasek's Job Content Questionnaire (JCQ). The strength of the association between each explanatory variable of interest and the metabolic syndrome was estimated by means of logistic regression, adjusted by sociodemographic factors and health related behaviors. Finally, the term of interaction between the explanatory variables of interest to estimate the effect of psychosocial stress at work on the association between night work and the presence of metabolic syndrome was included in the multivariate model. RESULTS: From a total number of participants, approximately 7% were night workers and 18% had exposure to the high-strain. The prevalence of metabolic syndrome in the study population was 33.0%. The highest prevalences of metabolic syndrome were presented by workers with 20 years or more of night work (43.1%), those exposed to the high-wear routine (36.8%), and among workers exposed to lower tertiary demand and control (35.5% and 33.7%, respectively). After all adjustments, night work 20 years was associated with a frequency of metabolic syndrome 36% higher than daytime work (95% CI: 1.09-1.69). Only exposure to high-wear work was independently associated with metabolic syndrome (OR: 1.16; 95% CI: 1.02-1.32). After mutual adjustments these associations were not altered. No interaction of psychosocial stress was identified in the association between work shift and metabolic syndrome (p value> 0.05). CONCLUSIONS: Night work over 20 years and job strain seem to independently influence the occurrence of metabolic syndrome. These findings reinforce the need to reduce job strain and mitigate the harmful effects of night work on health.